Indonesia, ASEAN Centrality and Global Maritime Fulcrum - Putri Auliya; Yohanes Sulaiman (Global Strategis, 2019)
Why Indonesia remains committed to maintain centrality of ASEAN in its Indo-Pacific strategy as a way to deter conflicts, especially in light of President Joko “Jokowi” Widodo’s famous proclamation of “Global Maritime Fulcrum?” The main thrust of “Global Maritime Fulcrum” doctrine is that facing shifting geopolitical and economic power from the West to Asia, Indoneia needed to face the challenge by putting Indonesia’s interest back to the forefront of global political and economic discourse. Yet, by the end of the day, Indonesia remained committed in pushing for the centrality of ASEAN especially in dealing with potential conflicts in the Indo-Pacific region. By stressing the centrality of ASEAN, meaning that Indonesia is attempting to strengthen cooperation between the members of ASEAN and crafting a cooperative regional framework, Indonesia and ASEAN as a whole may be able to reduce the tension due to the clashing interest of the United States and China in Indo-Pacific region.